Characterization, X-ray Absorption Spectroscopic Analysis and Photocatalytic Activity of Co/Zn Co-Doped TiO2 Nanoparticles Synthesized by One-Step Sonochemical Process - Wanichaya Mekprasart; Sorapong Pavasupree; C. K. Jayasankar; Balaji Rao Ravuri; Chakkaphan Wattanawikkam; Wisanu Pecharapa (Crystals, 2021)
A novel one-step preparation of sonochemical method was applied to synthesize Co/Zn co-doped TiO2 nanoparticles using a sonicator of 750 W, 20 kHz for 30 min at room temperature. The formation of the anatase TiO2 phase for all as-prepared samples was observed from XRD results with a crystalline size in nanoscale. The use of ultrasound allowed for the successful doping of both Co and Zn into the TiO2 lattice, which was confirmed by Synchrotron light including X-ray near edge structure (XANES) and Extended X-ray absorption fine structure (EXAFS) spectroscopy. Ti K-edge, Co K-edge, and Zn K-edge XANES spectra exhibited the dominating +4, +2, and +2 valence state of Ti, Co, and Zn in as-prepared samples, respectively. A detailed XANES and EXAFS data analysis give strong evidence that the Co/Zn dopants partially replace the Ti atom of the TiO2 host. The Co/Zn co-doping extends the light absorption of the host to the visible region and restricts the e+/h+ recombination. The photocatalytic activity of samples was tested for degradation of Rhodamine B dye solution under visible light irradiation. The as-synthesized of the co-doped catalyst was presented as highly efficient, with 2.5 and 5 times dye degradation compared with single-doped and bare TiO2.